Seeing the World Anew: Thomas Merton, Contemplation and the Spirituality of Place - Horan, Daniel P. (The Merton annual, 2025)
This article explores the relationship between place and contemplation. Beginning with St. Bonaventure (d. 1274) and his understanding of contemplation as speculatio, I engage Merton's writing with that of Douglas Christie on "the art of attention," allowing deeper exploration of place as it relates to contemplation. Then I develop a nascent "spirituality of place" that helps to expand our notion of contemplation and broaden our appreciation for Merton's insight and wisdom.